Pragmatic Strategies in Media Discourse - Bekberganova Khilola; Yusupova Sokhiba; Bekberganov Avazbek (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
Media discourse plays a crucial role in shaping public opinion and influencing social, political, and cultural perspectives. One of the key aspects of media language is the use of pragmatic strategies, which allow speakers and writers to convey meanings beyond literal expressions. This article examines the role of pragmatic strategies in media discourse, focusing on how language is used to persuade, inform, and manipulate audiences. The study analyzes key concepts such as implicature, presupposition, speech acts, framing, and politeness strategies, highlighting their functions in media communication. It also explores how these strategies contribute to the construction of ideology and influence audience interpretation.